A road base material for cold regions and a road base laid with the material
Patent Information
- Application Number
- CN202611124643.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
现有路面基层在寒冷地区冬季冻融循环作用下,孔隙水反复冻胀导致内部结构损伤,进而使强度衰减严重,使用寿命缩短30%-50%
本发明高强度底基层材料以钢渣粗骨料形成骨架结构并承担荷载,以黄河泥沙填充骨架空隙提高密实度,以固废胶凝材料胶结颗粒提供强度,使高强度底基层的7d无侧限抗压强度≥6.0MPa,抗压回弹模量≥1500MPa,压实度≥98%。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a road base material, and more particularly to a road base material for cold regions and a road base paved with the material. Background Technology
[0002] Currently, the main technical solutions for highway pavement base courses in cold regions are as follows: First, cement-stabilized crushed stone, using cement as the binder and natural crushed stone as aggregate; second, lime-fly ash stabilized crushed stone, using lime and fly ash as binders and natural crushed stone as aggregate; and third, asphalt-stabilized crushed stone, using asphalt as the binder and graded crushed stone as aggregate. However, these technologies have the following drawbacks: 1. Freeze-thaw damage is a prominent issue. In cold regions, the existing road base layer suffers from repeated freezing and thawing of pore water during winter, leading to internal structural damage, severe strength loss, and a 30%-50% reduction in service life.
[0003] 2. Widespread thermal shrinkage cracks. Existing semi-rigid pavement base courses (cement-stabilized, lime-fly ash-stabilized) have a large thermal shrinkage coefficient, which makes them prone to transverse cracks when the temperature drops suddenly. These cracks reflect onto the surface layer, thus affecting the service life of the pavement and driving comfort.
[0004] 3. Low utilization rate of solid waste. Existing road base layers mostly use single solid waste as raw material, and the amount of each type is low, failing to leverage the synergistic effect of multiple solid wastes and making it difficult to achieve high-value utilization.
[0005] 4. Lack of differentiated design for different layers. The existing road base structure is mostly made of a single material and is laid uniformly without differentiated mix design according to the needs of different functional layers, resulting in a mismatch between material performance and functional requirements.
[0006] Therefore, there is an urgent need to develop a road base material that is specifically designed for the freeze-thaw environment in cold regions, comprehensively utilizes Yellow River sediment and various industrial solid wastes, and achieves synergistic optimization of freeze resistance, crack resistance and load-bearing capacity through a layered and differentiated layout. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to provide a road base material that can utilize Yellow River sediment and various industrial solid wastes, and has the functions of load-bearing, crack resistance and frost resistance.
[0008] This invention provides a road base material for cold regions. The high-strength subbase material comprises Yellow River silt, steel slag coarse aggregate, and solid waste cementitious materials. The upper part of the high-strength subbase is a high-frost-resistant surface base, the high-frost-resistant surface base material comprising Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash, silica fume, and an air-entraining agent; or the high-strength subbase material comprises Yellow River silt, steel slag coarse aggregate, and solid waste cementitious materials. The upper part of the high-strength subbase is a semi-flexible crack-resistant base, the semi-flexible crack-resistant base material comprising Yellow River silt, steel slag medium aggregate, solid waste cementitious materials, and a polymer modifier; the upper part of the semi-flexible crack-resistant base is a high-frost-resistant surface base, the high-frost-resistant surface base material comprising Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash, silica fume, and an air-entraining agent.
[0009] Further, the fineness modulus of the Yellow River sediment is 1.0-2.2; the aging time of the steel slag coarse aggregate is >6 months, and the particle size is 5-20mm with continuous gradation; the solid waste cementitious material is slag powder, fly ash, carbide slag, and desulfurized gypsum; the aging time of the steel slag medium aggregate is >6 months, and the particle size is 0-10mm with continuous gradation; the polymer modifier is redispersible latex powder; the aging time of the steel slag fine aggregate is >6 months, and the particle size is 0-5mm with continuous gradation; the specific surface area of the silica fume is ≥15m². 2 / g, SiO2 content ≥85%, particle size 0.1-0.3μm.
[0010] Furthermore, the specific surface area of the slag powder in the solid waste cementitious material is ≥400m². 2 / kg, 7d activity index ≥70%, SO3 content ≤4.0%; the fly ash in the solid waste cementitious material is Class F low-calcium fly ash, with 45μm sieve residue ≤20% and loss on ignition ≤8%; the calcium carbide slag in the solid waste cementitious material has Ca(OH)2 ≥75% and moisture content ≤1.5%; the desulfurized gypsum in the solid waste cementitious material has CaSO4·2H2O content ≥85% and CaSO3·0.5H2O content ≤0.3%; the mass ratio of slag powder, fly ash, calcium carbide slag and desulfurized gypsum in the solid waste cementitious material is (40-60):(20-30):(10-20):(5-10).
[0011] Furthermore, the high-strength base layer material comprises, by weight percentage, the following components: The Yellow River contains 40%-55% silt. Steel slag coarse aggregate 35%-50% Solid waste cementitious materials: 10%-15%.
[0012] Furthermore, the semi-flexible crack-resistant base material comprises, by weight percentage, the following components: The Yellow River contains 45%-60% sediment. Aggregate content in steel slag is 25%-35%. Solid waste cementitious materials: 12%-18% Polymer modifier 3%-8%.
[0013] Furthermore, the high frost-resistant surface base material comprises, by weight percentage, the following components: The Yellow River contains 45%-55% sediment. Steel slag fine aggregate 15%-25% Solid waste cementitious materials 15%-20% 5%-10% fly ash Silica fume 2%-5%; The amount of air-entraining agent added is 0.015%-0.055% of the mass of the solid waste cementitious material.
[0014] Another object of the present invention is to provide a road base course comprising the above-mentioned road base course material.
[0015] Furthermore, when the road base course has a two-layer structure, the thickness ratio of the high-strength subbase course to the high-frost-resistant surface course is (2-3):(1-1.5), and the total thickness of the road base course is 25-40cm; when the road base course has a three-layer structure, the thickness ratio of the high-strength subbase course, the semi-flexible crack-resistant base course, and the high-frost-resistant surface course is (2-3):(1.4-2):(1-1.5), and the total thickness of the road base course is 30-50cm.
[0016] In the composite pavement base structure of this invention, the high-strength subbase has the largest thickness and bears the main load and stress diffusion function; the semi-flexible crack-resistant base has a moderate thickness and plays the role of absorbing thermal shrinkage stress and preventing crack reflection; the high frost-resistant surface base has the thinnest thickness and directly resists freeze-thaw cycles and water penetration.
[0017] Another objective of this invention is to provide a method for laying the aforementioned road base course. When the road base course has a two-layer structure, the laying method includes the following steps: High-strength subbase construction: Yellow River silt, steel slag coarse aggregate, and solid waste cementitious material are dry-mixed according to a predetermined mass percentage, then water is added and wet-mixed, with a water-cement ratio of 0.25-0.55. This mixture is then spread on the underlying layer, compacted, roughened, sprayed with an interface strengthening agent, and moisturized for curing. High-frost-resistant surface base construction: Yellow River silt, steel slag fine aggregate, solid waste cementitious material, fly ash, and silica fume are dry-mixed to obtain dry mixture II. An air-entraining agent is then mixed with water and added to dry mixture II for wet mixing, with a water-cement ratio of 0.25-0.55. This mixture is then spread on the high-strength subbase construction, compacted, and moisturized for curing. When the road base course has a three-layer structure, the laying method includes the following steps: High-strength subbase construction: According to a predetermined mass percentage... The process involves dry mixing Yellow River silt, steel slag coarse aggregate, and solid waste cementitious material, followed by wet mixing with water at a water-cement ratio of 0.25-0.55. This mixture is then spread on the underlying layer, compacted, roughened, sprayed with an interface reinforcing agent, and cured with moisture. For the semi-flexible crack-resistant base course: the Yellow River silt, steel slag medium aggregate, and solid waste cementitious material are dry mixed to obtain dry mixture I. A polymer modifier is then mixed with water and added to dry mixture I for wet mixing at a water-cement ratio of [missing information]. 0.25-0.55, then spread it on the high-strength base layer, compact it, then spray the interface enhancer and moisturize it for curing; High frost-resistant surface base layer construction: Dry mix Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash and silica fume to obtain dry mixture II, then mix the air-entraining agent with water and add it to dry mixture II for wet mixing, the water-cement ratio is 0.25-0.55, then spread it on the semi-flexible crack-resistant base layer, compact it, and then moisturize it for curing.
[0018] The beneficial effects of this invention are as follows: The high-strength subbase material of this invention uses steel slag coarse aggregate to form a skeleton structure and bear the load, fills the skeleton voids with Yellow River silt to improve density, and uses solid waste cementitious material to bind the particles and provide strength, so that the 7-day unconfined compressive strength of the high-strength subbase is ≥6.0MPa, the compressive resilience modulus is ≥1500MPa, and the compaction degree is ≥98%.
[0019] The semi-flexible crack-resistant base material of this invention is based on a high-strength base material with the addition of a polymer modifier. This polymer modifier forms a polymer-cement composite three-dimensional network structure in the mixture and interweaves with the cementitious products, thereby significantly improving the material's crack resistance and low-temperature deformation capacity. This results in a 7-day unconfined compressive strength of ≥4.0 MPa and a coefficient of thermal shrinkage ≤1.2 × 10⁻⁶. -5 / ℃, ultimate flexural strain ≥200με, can effectively absorb thermal shrinkage stress and prevent cracks from reflecting to the surface layer.
[0020] This invention relates to a high-frost-resistant surface base material, which incorporates fly ash, silica fume, and an air-entraining agent into a high-strength base material. Fly ash acts as a micro-aggregate filler, improving the pore structure; silica fume fills the micropores between the cementitious material and aggregates, refining the pore structure and reducing the capillary ratio by more than 30%, thereby significantly improving freeze-thaw cycle resistance; the air-entraining agent introduces microbubbles, effectively alleviating frost heave stress, resulting in a 7-day unconfined compressive strength ≥5.0 MPa and a permeability coefficient ≤1×10⁻⁶ for the high-frost-resistant surface base material. -9 With a speed of m / s, water absorption rate ≤5%, and freeze-thaw cycle count ≥250 times (and after 250 cycles, mass loss rate ≤5%, strength loss rate ≤20%), it can significantly extend the service life of road surfaces in cold regions.
[0021] The main raw materials used in this invention are all industrial solid waste. Based on a base course thickness of 40cm and a width of 12m per kilometer, it can dispose of about 12,000 tons of solid waste, replace about 10,000 tons of natural sand and gravel, reduce CO2 emissions by about 500 tons, and reduce costs by 30%-40% compared to traditional cement-stabilized crushed stone materials. Detailed Implementation
[0022] The following non-limiting embodiments are intended to enable those skilled in the art to more fully understand the invention, but do not limit the invention in any way.
[0023] The following Yellow River sediments were obtained through dredging or deposition and have a fineness modulus of 1.0-2.2.
[0024] The following steel slag coarse aggregate uses hot-quenched steel slag from the iron and steel industry with an aging time of more than 6 months and a continuous gradation of particle size of 5-20mm.
[0025] The following solid waste cementitious material is a compound made from slag powder, fly ash, carbide slag, and desulfurization gypsum; the specific surface area of the slag powder is ≥400 m². 2 / kg, 7d activity index ≥70%, SO3 content ≤4.0%; fly ash is Class F low-calcium fly ash, with 45μm sieve residue ≤20% and loss on ignition ≤8%; carbide slag has Ca(OH)2 ≥75% and moisture content ≤1.5%; desulfurized gypsum has CaSO4·2H2O content ≥85% and CaSO3·0.5H2O content ≤0.3%; The mass ratio of slag powder, fly ash, carbide slag and desulfurized gypsum is 50:25:15:10.
[0026] The aggregate in the following steel slag is hot-quenched steel slag from the iron and steel industry with an aging time of more than 6 months and a continuous gradation of 0-10mm particle size.
[0027] The polymer modifier described below is a redispersible latex powder, which is a copolymer of ethylene and vinyl acetate, purchased from Beijing Futen Technology Co., Ltd.
[0028] The following steel slag fine aggregate uses hot-quenched steel slag from the iron and steel industry with an aging time of >6 months and a continuous gradation of 0-5mm particle size.
[0029] The fly ash described below is a byproduct of coal-fired power plants.
[0030] The following silica ash is a byproduct of the production of industrial silicon or ferrosilicon alloys and has a specific surface area ≥15m². 2 / g, SiO2 content ≥85%, particle size 0.1-0.3μm.
[0031] The following air-entraining agent is a rosin thermal polymer air-entraining agent, purchased from Beijing Futen Technology Co., Ltd.
[0032] The following interface enhancer is a mixture of styrene-butadiene emulsion and cement slurry, purchased from Beijing Futen Technology Co., Ltd.
[0033] Example 1 A method for laying a base course for light traffic roads in cold regions, the method comprising the following steps: Step 1: High-strength subbase construction. By weight percentage, dry mix 48% Yellow River silt, 42% steel slag coarse aggregate, and 10% solid waste cementitious material at a low speed of 35 r / min for 3 minutes, then dry mix at a medium speed of 70 r / min for 2 minutes. Add water and wet mix at 90 r / min for 3 minutes, achieving a water-cement ratio of 0.35. Spread this mixture on the underlying layer, compact it to a compaction degree ≥95%, then roughen the surface and spray an interface strengthening agent at a rate of 0.8 kg / m². 2 After covering with geotextile and watering for 7 days, a high-strength base layer with a thickness of 18cm was obtained.
[0034] Step 2: Construction of the high frost-resistant base course. Mix 54% Yellow River silt, 20% steel slag fine aggregate, 15% solid waste cementitious material, 8% fly ash, and 3% silica fume at a low speed of 35 r / min for 3 minutes, then at a medium speed of 70 r / min for 2 minutes to obtain dry mixture II. Add the air-entraining agent and water to dry mixture II and wet mix at 90 r / min for 4 minutes. The amount of air-entraining agent added is 0.02% of the mass of the solid waste cementitious material, and the water-cement ratio is 0.35. Then, spread this mixture on the high-strength subbase, with a compaction degree ≥95%. Cover with geotextile and cure with water for 14 days to obtain a 9cm thick high frost-resistant base course.
[0035] Example 2 A method for laying a base course for heavy-traffic roads in cold regions, the method comprising the following steps: Step 1: High-strength subbase construction. By weight percentage, dry mix 48% Yellow River silt, 42% steel slag coarse aggregate, and 10% solid waste cementitious material at a low speed of 35 r / min for 3 minutes, then dry mix at a medium speed of 70 r / min for 2 minutes. Add water and wet mix at 90 r / min for 3 minutes, achieving a water-cement ratio of 0.35. Spread this mixture on the underlying layer, compact it to a compaction degree ≥95%, then roughen the surface and spray an interface strengthening agent at a rate of 0.8 kg / m². 2 After covering with geotextile and watering for 7 days, a high-strength base layer with a thickness of 18cm was obtained.
[0036] Step Two: Construction of Semi-Flexible Crack-Resistant Base Layer. Dry mix 52% Yellow River silt, 30% steel slag aggregate, and 15% solid waste cementitious material at a low speed of 35 r / min for 3 minutes, then dry mix at a medium speed of 70 r / min for 2 minutes to obtain dry mixture I. Next, mix 3% polymer modifier with water and add it to dry mixture I, then wet mix at 90 r / min for 3 minutes, achieving a water-cement ratio of 0.35. Spread this mixture on the high-strength subbase, compact it to a compaction degree ≥98%, and then spray an interface reinforcing agent at a rate of 0.5 kg / m². 2 After covering with geotextile and watering for 10 days, a semi-flexible crack-resistant base layer with a thickness of 13cm was obtained.
[0037] Step 3: Construction of the high frost-resistant base course. Mix 54% Yellow River silt, 20% steel slag fine aggregate, 15% solid waste cementitious material, 8% fly ash, and 3% silica fume at a low speed of 35 r / min for 3 minutes, then at a medium speed of 70 r / min for 2 minutes to obtain dry mixture II. Add the air-entraining agent and water to dry mixture II and wet mix at 90 r / min for 4 minutes. The amount of air-entraining agent added is 0.02% of the mass of the solid waste cementitious material, and the water-cement ratio is 0.35. Then, spread this mixture on the semi-flexible crack-resistant base course, with a compaction degree ≥95%. Finally, cover with geotextile and cure with water for 14 days to obtain a 9cm thick high frost-resistant base course.
[0038] Comparative Example 1 The difference from Example 2 is that the high frost-resistant base layer is made of 54% Yellow River silt, 23% steel slag fine aggregate, 18% solid waste cementitious material, 5% silica fume and air-entraining agent, and contains no fly ash.
[0039] Comparative Example 2 The difference from Example 2 is that the high frost-resistant base layer is made of 54% Yellow River silt, 20% steel slag fine aggregate, 16% solid waste cementitious material, 10% fly ash and air-entraining agent, and contains no silica fume.
[0040] Comparative Example 3 The difference from Example 2 is that the high frost-resistant base layer made of Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash and silica fume does not contain an air-entraining agent.
[0041] The following performance tests were conducted on the road base courses laid in Examples 1-2 and Comparative Examples 1-3. The 7-day unconfined compressive strength, 28-day unconfined compressive strength, compressive strength loss rate after 5 freeze-thaw cycles, and drying shrinkage coefficient were determined according to the "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG 3441-2024). The results are shown in Table 1.
[0042] Table 1 Table 1 shows that the road base layer laid by this invention has load-bearing, crack-resistant, and frost-resistant functions. Furthermore, the synergistic effect of fly ash, silica fume, and the air-entraining agent is indispensable: Comparative Example 1 (without fly ash) had the lowest strength and significantly reduced frost resistance, with a loss rate of 25.63%; Comparative Example 2 (without silica fume) showed a freeze-thaw loss rate of 28.47%, indicating that silica fume significantly contributes to frost resistance; Comparative Example 3 (without air-entraining agent) had the highest freeze-thaw loss rate (32.26%), proving that the introduction of microbubbles by the air-entraining agent is crucial for alleviating frost heave stress.
Claims
1. A road base material for cold regions, characterized in that: High-strength subbase materials include Yellow River silt, steel slag coarse aggregate, and solid waste cementitious materials; The upper part of the high-strength subbase is a high-frost-resistant surface base, and the high-frost-resistant surface base material includes Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash, silica fume, and air-entraining agent. Alternatively, high-strength subbase materials include Yellow River silt, steel slag coarse aggregate, and solid waste cementitious materials; The upper part of the high-strength base course is a semi-flexible crack-resistant base course, and the semi-flexible crack-resistant base course material includes Yellow River silt, steel slag aggregate, solid waste cementitious materials, and polymer modifiers. The upper part of the semi-flexible crack-resistant base layer is a high frost-resistant surface base layer, and the high frost-resistant surface base layer material includes Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash, silica fume, and air-entraining agent.
2. The road base material according to claim 1, characterized in that: The fineness modulus of the Yellow River sediment is 1.0-2.2; The steel slag coarse aggregate has an aging time of >6 months and a particle size of 5-20mm with continuous gradation; The solid waste cementing material is slag powder, fly ash, carbide slag and desulfurized gypsum; The aggregate in the steel slag has an aging time of >6 months and a particle size of 0-10mm with continuous gradation. The polymer modifier is a redispersible latex powder; The steel slag fine aggregate has an aging time of >6 months and a particle size of 0-5mm continuous gradation; The specific surface area of the silica fume is ≥15m². 2 / g, SiO2 content ≥85%, particle size 0.1-0.3μm.
3. The road base material according to claim 2, characterized in that: The specific surface area of the slag powder in the solid waste cementitious material is ≥400m². 2 / kg, 7d activity index ≥70%, SO3 content ≤4.0%; The fly ash in the solid waste cementitious material is Class F low-calcium fly ash, with a 45μm sieve residue ≤20% and a loss on ignition ≤8%; The solid waste cementitious material contains calcium carbide slag with a Ca(OH)2 content ≥ 75% and a moisture content ≤ 1.5%. The solid waste cementitious material contains desulfurized gypsum with a CaSO4·2H2O content ≥85% and a CaSO3·0.5H2O content ≤0.3%. The mass ratio of slag powder, fly ash, carbide slag and desulfurized gypsum in the solid waste cementitious material is (40-60): (20-30): (10-20): (5-10).
4. The road base material according to claim 1, characterized in that: The high-strength base layer material comprises the following components by weight percentage: The Yellow River contains 40%-55% silt. Steel slag coarse aggregate 35%-50% Solid waste cementitious materials: 10%-15%.
5. The road base material according to claim 1, characterized in that: The semi-flexible crack-resistant base material comprises the following components by weight percentage: The Yellow River contains 45%-60% sediment. Aggregate content in steel slag is 25%-35%. Solid waste cementitious materials: 12%-18% Polymer modifier 3%-8%.
6. The road base material according to claim 1, characterized in that: The high frost-resistant base material comprises the following components by weight percentage: The Yellow River contains 45%-55% sediment. Steel slag fine aggregate 15%-25% Solid waste cementitious materials 15%-20% 5%-10% fly ash Silica fume 2%-5%; The amount of air-entraining agent added is 0.015%-0.055% of the mass of the solid waste cementitious material.
7. A road base course, characterized in that: The road base material includes any one of claims 1-6.
8. The road base course according to claim 7, characterized in that: When the road base course has a two-layer structure, the thickness ratio of the high-strength subbase course to the high-frost-resistant surface base course is (2-3):(1-1.5), and the total thickness of the road base course is 25-40cm. When the road base course has a three-layer structure, the thickness ratio of the high-strength subbase course, the semi-flexible crack-resistant base course, and the high frost-resistant surface base course is (2-3):(1.4-2):(1-1.5), and the total thickness of the road base course is 30-50cm.
9. The method for laying the road base course as described in claim 7 or 8, characterized in that: When the road base layer has a two-layer structure, the paving method includes the following steps: High-strength subbase construction: According to the predetermined mass percentage, dry mix the Yellow River silt, steel slag coarse aggregate and solid waste cementitious material, then add water and wet mix, with a water-cement ratio of 0.25-0.
55. Then spread it on the subbase, compact it, roughen it, spray the interface strengthening agent, and moisturize and cure it. High frost-resistant base course construction: Dry mix Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash and silica fume to obtain dry mixture II. Then mix air-entraining agent with water and add it to dry mixture II for wet mixing. The water-cement ratio is 0.25-0.
55. Then spread it on the high-strength base course, compact it, and then keep it moist and cured. When the road base layer has a three-layer structure, the paving method includes the following steps: High-strength subbase construction: According to the predetermined mass percentage, dry mix the Yellow River silt, steel slag coarse aggregate and solid waste cementitious material, then add water and wet mix, with a water-cement ratio of 0.25-0.
55. Then spread it on the subbase, compact it, roughen it, spray the interface strengthening agent, and moisturize and cure it. Semi-flexible crack-resistant base course construction: Dry mix Yellow River silt, steel slag aggregate and solid waste cementitious material to obtain dry mixture I. Then mix polymer modifier with water and add to dry mixture I for wet mixing. The water-cement ratio is 0.25-0.
55. Then spread it on the high-strength base course, compact it, and then spray interface reinforcement agent and moisturize and cure. High frost-resistant base course construction: Dry mix Yellow River silt, steel slag fine aggregate, solid waste cementitious materials, fly ash and silica fume to obtain dry mixture II. Then, mix air-entraining agent with water and add it to dry mixture II for wet mixing. The water-cement ratio is 0.25-0.
55. Then, spread it on the semi-flexible crack-resistant base course, compact it, and then keep it moist and cured.